Implementing AMETTA (Active, Joyful, and Unstressed) in Increasing Learning Activity and Outcomes - Yenni Hasnah; Pirman Ginting; Selamat Husni Hasibuan (AL-ISHLAH: Jurnal Pendidikan, 2021)
This research aims to analyze the learning model's practice and its effect on increasing student activity and learning outcomes in listening subjects. This study employed quasi-experimental research with a non-equivalent control group design. The data were gained using observation and tests. It is analyzed by reflection and statistical test of SPPS. The results show that the application of the AMETTA learning model effectively develops student learning activities and outcomes. The result of hypothesis testing with sig. (2-tailed) was 0.033 (˂ 0.05) It indicates that Ho is rejected. Thus, there is a significant difference between the average student learning outcomes in the experimental and control classes. In other words, the application of AMETTA learning model has a significant effect on students’ learning outcomes.